Comparison of Imazalil Removal onto Montmorillonite and Nanomontmorillonite and Adsorption Surface Sites Involved: An Approach for Agricultural Wastewater Treatment - Gamba, Martina (2015)
To remove fungicide Imazalil (IMZ) (commercial formulation) from agricultural wastewater, adsorption was performed and compared among montmorillonite (Mt) and four organo-Mts (OMts), with different octadecyltrimethylammonium (ODTMA) loadings. The agglomerates size increase of OMts with respect to Mt found encourages the use of the former in agricultural wastewater treatment. Characterization of the OMts adsorbents by powder X-ray diffraction, infrared spectroscopy, and thermogravimetric analyses, indicated that ODTMA was present in the interlayer with different molecular arrangements, a diminution of the thermal stability of the OMts and an increase of ODTMA loading being observed at the same time. Zeta potential measurements showed electric surface charge reversion from negative to positive when the surfactant loading exceeded 100% of the clay cation exchange capacity (CEC). The IMZ adsorption on the raw Mt showed high pH dependence and affinity toward the fungicide, while OMts showed best IMZ adsorption capacity at high IMZ concentrations inversely related with the ODTMA loading. The characterization of IMZ−adsorbed samples indicated that for IMZ−Mt the interaction between IMZH+ and the siloxane surface was electrostatic. For IMZ−OMt samples the presence of new XRD and FTIR peaks suggested different IMZ interlayer arrangements and direct interaction with the surface, respectively. Analysis of zeta potential measurements indicated synergetic effects between the ODTMA and IMZ molecules at the external surface.